FRI0312 Arthritis in primary sjÖgren's syndrome: characteristics, outcome and treatment from french multicenter retrospective study. (12th June 2018) - Mirouse, A.; Séror, R.; Vicaut, E.; Mariette, X.; Dougados, M.; Fauchais, A.-L.; Deroux, A.; Costedoat-Chalumeau, N.; Sellam, J.; Arlet, J.-B.; Lavigne, C.; Fain, O.; et al.
Abstract : Background: Primary Sjogren's syndrome (pSS) is a chronic inflammatory disorder characterised by diminished lacrimal and salivary gland functions. Joint involvement is reported in 20% to 60% of pSS patients, and among them one third of patients present synovitis. There is a lack of data concerning therapeutic management during pSS-associated synovitis. Objectives: To describe the characteristics and the outcome of pSS associated arthritis and to compare the efficacy of different therapeutic regimen. Methods: We conducted a retrospective study using Club Rhumatisme and Inflammation (CRI) and French Internal Medicine Society (SNFMI) networks. All patients with a diagnosis of primary Sjögren's Syndrome (pSS) and at least one clinical and/or echographic synovitis were included. Patients with synovitis (cases) were compared to pSS patients without synovitis (controls). Results: 57 patients (93% women) were included with a median age of 54 years. 45–63 Patients with synovitis had more frequently lymph node enlargement (12.3% vs. 1.8%, p=0.007) and a higher ESSDAI score (8 6–12 vs. 2, 1–4 p<0.0001). There was no difference concerning CRP levels, rheumatoid factor and CCP-antibodies positivity. Among 57 patients with synovitis, 101 lines of various treatments have been used during the follow-up of 40 [22.5–77] months. First line treatment consisted in steroids alone (3.5%), steroids in association (79%) with hydroxychloroquine (HCQ) (49%), methotrexate (MTX) (35%), rituximab (RTX) (5.3%) or other immunosuppressive drugs (7%). The number of complete/partial joint responses significantly increased considering the number of overall lines of treatment for MTX, HCQ and RTX: 52% for the first line, 76% for the second line and 83% for the third line (p<0.05), and data were similar considering each drug separately. There was no difference of efficacy between HCQ, MTX, and RTX concerning tender and swollen joint count, CRP level, ESSDAI score and steroids sparing effect at the end of each drug regimen. We performed a propensity score based analysis to determine whether HCQ, MTX, or RTX treatment was associated with better joint outcome. No difference could be shown for the joint response between three treatment regimen (MTX vs. HCQ, OR 1.55 [0.18–13.55], p=0.69; MTX vs. RTX, OR 5.08 [0.49–52.17], p=0.17; HCQ vs. RTX OR 3.28 [0.28–38.02], p=0.34). All 3 treatments (HCQ, MTX, and RTX) were associated with a significant reduction of ESSDAI score and a significant steroids-sparing effect. Conclusions: pSS articular manifestations may include synovitis which could mimic rheumatoid arthritis but differ by the absence of structural damage. Even if the use of HCQ, MTX, and RTX seem to be effective for joint involvement, the best regimen remains to be determined. Disclosure of Interest: None declared